Life in the real world : 5-minute devotions for teens - Ritter, Eileen, 1943- (St. Louis : Concordia Pub. House, 1997)
A collection of meditations with scripture references, practical applications, and prayers, focusing on such real-life issues as friends and family, dating, prejudice, anger, rules, and faith.
Keywords: Teenagers -- Prayers and devotions; Prayer books and devotions; Christian life